Tunability of the self-assemblies of porous polygon-like zinc cobaltite architectures using mixed solvents for high-performance supercapacitors. (April 2022) - Gedi, Sreedevi; Manne, Ravi; Manjula, G.; Reddy, L. Veeranjaneya; Reddy, C. Parthasaradhi; Marraiki, Najat; Kim, Woo Kyoung; Mallikarjuna, K.; Pratap Reddy, M. Siva
Abstract: The specific morphology and unique properties of functional materials attracts researchers to explore their applicability in diverse applications. The formation mechanism of the solvent-dependent controlled morphologies of two different self-assemblies of ZnCo2 O4 microstructures has been demonstrated. Polygon-like shapes are formed by the self-assemblies of porous nanoparticles, while polygons formed via a similar self-assembly process by nanosheets instead of nanoparticles. The physicochemical properties such as the structure, surface properties and morphologies of both samples were studied and compared. The electrochemical properties of the supercapacitor based on ZnCo2 O4 microstructures were investigated using cyclic voltammetry, charge-discharge characteristics, and impedance spectroscopy methods. The cyclic stability of the synthesized electrode over 4000 cycles was studied. A comparison of the electrochemical studies showed the enhanced performance of the polygons with a porous structure (areal capacitance of 24.4 mF cm −2 at 50 μA cm −2 ) when compared to its counterpart (areal capacitance of 20.1 mF cm −2 at 50 μA cm −2 ). Highlights: Solvent-dependent morphology controlled ZnCo2 O4 microstructures have been prepared. Polygon-like shapes were formed by porous nanoparticles and nanosheets. The cyclic stability of the as-synthesized electrode was studied over 4000 cycles.